A Review of Organic Agriculture Industry in Malaysia and Gross Margin between Organic and Conventional Plantation - RAHMAT, SITI RAHYLA; KHAN, HAMAD HASUL; BADARUDDIN, RADIN FIRDAUS RADIN; MOHAMAD, MOHD FIKRI; SAMSURIJAN, MOHAMAD SHAHARUDIN (The journal of contemporary issues in business and government, 2021)
The objective of this study are 1) To review the definition of organic farming 2) To investigate the international and local standard for organic food and 3) To compare gross margin between organic and inorganic paddy farming. Using field evaluation and interview techniques, this study conducted a study on 3 organic farms and 27 inorganic paddy farms in Malaysia. Two leading organic agriculture regulators in the world are IFOAM and USDA, IFOAM allows private standard setters to define their additional criteria and USDA does not allow others to set a standard that is above the federal. This study also laid out a few organic accreditations in several Asian countries including Thailand, Indonesia, Cambodia, Japan, India, and China. Field evaluation of conventional and organic paddy plantation are discussed and it is found that organic plantation earned less gross margins (13.5 %) as compared to inorganic farming. This study may give some inputs for the Research and Development (R&D) department to improve the organic farming activities and how to reduce its cost and increase its gross margin. Organic farming is important as it is sustainable to lure bio-economy strategy and food security in Malaysia as laid out in National Agricultural Policy.